2006
DOI: 10.1111/j.1439-0450.2006.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Presence ofail,ystAandystBGenes inYersinia enterocoliticaStrains Isolated from Aborting Sows and Aborted Fetuses

Abstract: Forty-five Yersinia enterocolitica strains isolated from aborted fetuses and placentas and from vaginal and rectal swabs of aborting sows were subjected to serotyping, biochemical typing and polymerase chain reaction multiplex analyses to detect the presence of the ail, yst A and ystB genes. The isolates were recovered from the internal organs (tonsil, lung, liver, spleen, kidney, mesentheric lymph nodes, small intestine and rectal intestine) of 18 (18.6%) of 97 aborted fetuses examined, two (8%) of 25 aborted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
(67 reference statements)
2
21
2
1
Order By: Relevance
“…A lower prevalence has been reported in Italy (13%), Greece (13%), and Poland (4%) (Bonardi et al, 2003;Kechagia et al, 2007;Kot et al, 2007). Y. enterocolitica 4=O:3 was the only bioserotype found in the present study and has also been shown to be the most common type in slaughtered pigs in Finland, Germany, Greece, Italy, Norway, Switzerland, and Poland (Fredriksson-Ahomaa et al, 2000Bonardi et al, 2003;Gü rtler et al, 2005;Nesbakken et al, 2006;Platt-Samoraj et al, 2006;Kechagia et al, 2007). However, bioserotype 3=O:5,27 dominates in slaughter pigs in the United Kingdom (Milnes et al, 2008).…”
Section: Discussioncontrasting
confidence: 52%
“…A lower prevalence has been reported in Italy (13%), Greece (13%), and Poland (4%) (Bonardi et al, 2003;Kechagia et al, 2007;Kot et al, 2007). Y. enterocolitica 4=O:3 was the only bioserotype found in the present study and has also been shown to be the most common type in slaughtered pigs in Finland, Germany, Greece, Italy, Norway, Switzerland, and Poland (Fredriksson-Ahomaa et al, 2000Bonardi et al, 2003;Gü rtler et al, 2005;Nesbakken et al, 2006;Platt-Samoraj et al, 2006;Kechagia et al, 2007). However, bioserotype 3=O:5,27 dominates in slaughter pigs in the United Kingdom (Milnes et al, 2008).…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast with the studies of pathogenic strains of Y. enterocolitica O:3 by Thoerner et al (2003) and Platt-Samoraj et al (2006) where the ystA gene was identified in 100% and 99%, respectively, in our study the ystA gene was found in only 83% of isolates. A study of reference strains showed the The yadA and virF genes were identified in 79% and 49% of isolates of Y. enterocolitica O:3, respectively, the yadA gene was found only in pathogenic reference strain of Y. enterocolitica CCM 5671, and the virF gene was not identified in any of the reference strains.…”
Section: Resultscontrasting
confidence: 99%
“…The ail gene encodes Ail protein, it occurs only in the pathogenic strains of Y. enterocolitica. This protein participates in bacterial adhesion to mammalian cells, facilitates their invasion into eukaryotic cells, and intensifies their resistance to the bacteriocidal effects of complement (Platt-Samoraj et al 2006). The rfbC gene is localised on the chromosome only in pathogenic strains of Y. enterocolitica serotype O:3 (Weynants et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…None of the examined isolates was ystB-positive. Platt-Samoraj et al (15) found the presence of ail, ystA, and ystB virulence markers in Y. enterocolitica strains isolated from aborting sows and aborted foetuses. Among 45 Y. enterocolitica isolates, 40, belonging to biotype 1A, contained only the ystB gene, whereas the remaining five, belonging to bioserotype 4/O:3, carried ail and ystA genes.…”
Section: Discussionmentioning
confidence: 99%